Utilização do jogo digital cidade verde no ambiente ensino e aprendizagem para a conscientização da conservação e preservação dos recursos naturais do meio ambiente - ARAÚJO, Karine da Silva (2019)
The introduction of Information and Communication Technologies (ICT) and the educational potentials of the interaction through hypermedia interface networked by the Internet foster the emergence of new socio-educational practices, taking into account all educational environments, not just schools. The research presents as an object of study the digital game Green City, an online game that has a concept approach to Environmental Education and how daily activities can help in the preservation of the environment. Qualitative and quantitative research was adopted as methodology in conjunction with the exploratory and field research phases. As instruments for data collection were used questionnaires, interface evaluation, observation with annotations, videos and photographs, focus group and online questionnaire. The research presents the results obtained through the usability test. It was considered that the digital game Green City presents factors necessary for this form of application, where it provides motivation, participation and involvement of the children with the studied content. However, the set of techniques used in the usability test presented some aspects in the interface that can be improved and thus provide a better experience for the user. Through the results, we reached positive conclusions regarding the application of digital game in teaching and learning environments, as well as ideas of improvements regarding the interface of the game.